1992
DOI: 10.1021/bi00136a012
|View full text |Cite
|
Sign up to set email alerts
|

Helical epitope of the group B meningococcal .alpha.(2-8)-linked sialic acid polysaccharide

Abstract: The immunological properties of the group B meningococcal alpha(2-8)-linked sialic acid polysaccharide have been rationalized in terms of a model where the random coil nature of the polymer can be described by the presence of local helices. The conformational versatility of the alpha NeuAc(2-8)alpha NeuAc linkage has been explored by NMR studies at 600 MHz in conjunction with potential energy calculations for colominic acid, an alpha(2-8)NeuAc polymer, and the trisaccharide alpha NeuAc(2-8)alpha NeuAc(2-8)beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
125
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 19 publications
21
125
0
Order By: Relevance
“…The conformations of the trisialic acids in the two antigenbinding sites are essentially identical. The dihedral angles of a helical conformation reported in a previous docking model study are Ϫ45°, 130°, 60°, and 60°, respectively (14). In this structure, however, the dihedral angles of the interacting trisialic acid demonstrate a rather unfolded conformation and differ greatly from those mentioned above for the proposed helical conformation (underlined in Table 3).…”
Section: Direct and Water-mediated Carbohydrate Recognition Bymentioning
confidence: 48%
See 1 more Smart Citation
“…The conformations of the trisialic acids in the two antigenbinding sites are essentially identical. The dihedral angles of a helical conformation reported in a previous docking model study are Ϫ45°, 130°, 60°, and 60°, respectively (14). In this structure, however, the dihedral angles of the interacting trisialic acid demonstrate a rather unfolded conformation and differ greatly from those mentioned above for the proposed helical conformation (underlined in Table 3).…”
Section: Direct and Water-mediated Carbohydrate Recognition Bymentioning
confidence: 48%
“…Flexible helical structures were suggested by nuclear magnetic resonance (NMR) analyses with the aid of molecular modeling and dynamics calculations. Two groups independently reported helical structures, but the pitches of the proposed helices are significantly different (13,14). More recently, another helical structure was suggested based on trisialic acid analysis using high field NMR with molecular dynamics simulations (15).…”
mentioning
confidence: 99%
“…The requirement of Dectin-1 for decasaccharides or longer oligosaccharides of glucans is reminiscent of the properties of antibodies specific for another homo-oligomer, ␣2-8-linked polysialic acid. NMR studies together with potential energy calculations led to the postulate that the unusual oligosaccharide length dependence for recognition by these antibodies arises from the existence of a conformational epitope, a high order local helix (37).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MARCKS, it has been shown that PSA associates with liposomal membranes and penetrates lipid bilayers (35)(36)(37). This intimate interaction of PSA with membranes is mediated or facilitated by the helical and random-coil conformations of PSA (38). Based on the similar properties of PSA and MARCKS to insert into lipid bilayers, we propose that MARCKS and PSA interact at or within the plasma membrane from opposite sides.…”
Section: Discussionmentioning
confidence: 90%